Adult and juvenile bearded capuchin monkeys handle stone hammers differently during nut‐cracking. Issue 7 (26th May 2020) - Fragaszy, Dorothy M.; Barton, Sophie A.; Keo, Sreinick; Patel, Rushi; Izar, Patrícia; Visalberghi, Elisabetta; Haslam, Michael
Abstract: Wild bearded capuchin monkeys ( Sapajus libidinosus ) habitually use stone hammers to crack open palm nuts and seeds on anvils. This activity requires strength, balance, and precise movement of a large stone with respect to the item placed on an anvil. We explored how well young monkeys cope with these challenges by examining their behavior and the behavior of adults while they cracked palm nuts using a stone. Using video records, we compared actions of six juvenile (2–5 years) and six adult (7+ years) wild monkeys during their first 20 strikes with one unfamiliar ellipsoid, quartzite stone (540 g), and the outcomes of these strikes. Compared with adults, juveniles cracked fewer nuts, performed a more diverse set of exploratory actions, and less frequently placed one or both hands on top of the stone on the downward motion. Adults and juveniles displayed similar low frequencies of striking with a slanted trajectory, missing the nut, and losing control over the nut or stone after striking. These findings indicate that young monkeys control the trajectory of a stone adequately but that is not sufficient to crack nuts as effectively as adults do. Compared with juveniles, adults more quickly perceive how to grip the stone efficiently, and they are able to adjust their grip dynamically during the strike. Young monkeys develop expertise in the latter aspects of cracking nuts over the course of several years of regular practice, indicating that perceptual learning about these aspects of percussion occurs slowly. Juvenile and adult humans learning to use stones to crack nuts also master these features of cracking nuts very slowly. Abstract : Wild bearded capuchin monkeys ( Sapajus libidinosus ) were video recorded striking palm nuts with stones to crack them. Adults more frequently adjusted their grip on the stone dynamically during the strike; juveniles performed a more diverse set of exploratory actions. Developing adult levels of expertise in handling the stone while striking nuts apparently takes bearded capuchin monkeys several years.